KEPEMIMPINAN KYAI DALAM MENGELOLA MANAJEMEN PENDIDIKAN PESANTREN DI ERA DIGITAL - Alya Annisa Ramadhani; Muhammad Iqbal; Paisal Zunaidi; Adil Fathi Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The advancement of the digital era has significantly transformed the management of Islamic boarding schools (pesantren), positioning the leadership of the kyai as a crucial factor in balancing tradition and innovation. This conceptual study employs a library research approach to examine how kyai manage pesantren education by integrating traditional values with modern technological developments. The findings indicate that kyai leadership extends beyond charismatic authority; it includes visionary and adaptive capacities necessary for navigating digitalization. Kyai play essential roles in policy formulation, curriculum transformation, digital administrative governance, and ensuring that technological integration remains aligned with pesantren culture. The study identifies several challenges, including digital literacy gaps, resistance to change, and maintaining the ethical and character-based learning traditions unique to pesantren. This review concludes that the success of pesantren in the digital era depends largely on the kyai’s ability to harmonize classical Islamic values with contemporary technological demands.